Study the epistemological contributions of agroecology in Bucaramanga - Lara Calderón, Pablo Lleral; Portilla Martínez, Jose Vicente (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
The agricultural sector was prepared to adopt foreign agrochemicals based on food shortages, which apparently revolutionized the agricultural activity, for a better quality of life. The objectives are based on the following: review documentary sources to know the current episteme of agroecology, classify the information in sections, build the discourse based on the object of study, analyze the documentary results. The research is qualitative, the methodology is documentary based on the review of periodic sources inherent to agroecology in the geographical context of Bucaramanga, Department of Santander, Colombia.